Playing Harry Potter : essays and interviews on fandom and performance - Brenner, Lisa S. (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2015)
"Through classroom activities, wizard rock concerts and organizations like the Harry Potter Alliance, Harry Potter fans are using creativity to positively impact the world. This collection of essays and interviews examines how playful fandom not only re-imagines the canon but also challenges consumerism, questions notions of identity and fosters participatory culture"--
Includes bibliographical references and index.
Keywords: Rowling, J. K. -- Characters; Potter, Harry -- (Fictitious character); Children's stories, English -- Appreciation; Fantasy fiction, English -- Appreciation